Do Sharia Investments Promote Responsible Consumption? A Structural Equation Modeling Approach - Indra Rajasa, Muhammad Attar; Tamamala, Zailan Basri; Ratnasari, Ririn Tri (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
on progress